Temperature dependence of dynamical permeability characterization of magnetic thin films using shorted microstrip line probe. (17th October 2017) - Li, Xiling; Li, Chengyi; Chai, Guozhi
Abstract: A temperature dependence microwave permeability characterization system of magnetic thin film up to 10 GHz is designed and fabricated. This system can be used at temperatures ranging from room temperature to 200 °C, and is based on a shorted microstrip probe, which is made by microwave printed circuit board. Without contacting the magnetic thin films to the probe, the microwave permeability of the film can be detected without any limitations of sample size and with almost the same accuracy, as shown by comparison with the results obtained from a shorted microstrip transmission-line fixture. The complex permeability can be deduced by an analytical approach from the measured reflection coefficient of a strip line ( S 11 ) with and without a ferromagnetic film material on it. The procedures are the same with the shorted microstrip transmission-line method. The microwave permeability of an oblique deposited CoZr thin film was investigated with this probe. The results show that the room temperature dynamic permeability of the CoZr film is in good agreement with the results obtained from the established short-circuited microstrip perturbation method. The temperature dependence permeability results fit well with the Landau–Lifshitz–Gilbert equation. Development of the temperature-dependent measurement of the magnetic properties of magnetic thin film may be useful for the high-frequency application of magnetic devices at high temperatures.